Inter-ethnic Fertility Spillovers and the Role of Forward-looking Behavior: Evidence from Peninsular Malaysia - Emily A. Beam; Slesh Shrestha (Institute for the Study of Labor (IZA), 2016)
Demographic pressures can create competition for limited private and public resources and exacerbate pre-existing inter-ethnic tensions. At the same time, inter-ethnic competition may influence individual fertility decisions. Using the variation in birth rates in Malaysia induced by the Chinese lunar calendar, we document a 12.7-percent rise in births among ethnic Chinese in dragon years, which are considered auspicious. We find a negative fertility response from Malays – for every additional Chinese new-born child, Malays reduced their fertility by 0.30 children. We estimate the elasticity of this inter-ethnic fertility spillover (-0.15), and we find strongly suggestive evidence that pressure on resources was an important driver of these spillovers. The Malay response was greatest in areas where resources were more limited, and in areas with lower public investments. These results suggest that households are forward-looking in their fertility decisions, and they point to the potential role of governments in reducing ethnic tension through policies that increase private and public resources.
Keywords: D74; J13; J15; O15; O17; 330; fertility timing; ethnic competition; spillover; Chinese zodiac; public resources; Malaysia